PROBLEMATICS OF ENTERPRISE DEVELOPMENT IN THE ECONOMY OF KNOWLEDGE BASED ON LOGISTIC APPROACH - E. A. Balchik (Real Economics Publishing House, 2018)
The theoretical approach of the knowledge economy to the development of the strategy of industrial enterprises on the basis of the logistical methodology are covered. The definition of strategy and strategic planning for the knowledge economy is presented. The process of strategy development is characterized and the algorithm of strategic planning of an industrial enterprise is proposed taking into account the knowledge economy.